Synthesis and reactions of new 2-hydroxymethyldimethoxyindoles. Issue 1 (7th January 2016) - Bingul, Murat; Kumar, Naresh; Black, David StC.
Abstract: Lithium aluminium hyride was used as a reducing agent to prepare a range of 2-hydroxymethyldimethoxyindole derivatives from the related methyl esters. Acid-catalysed reactions of these indole-2-methanols yielded indolo-cyclotriveratrylenes linked through C-2 and C-3. The related indole-2-carbaldehydes were prepared via oxidation of the indole-2-methanols in the presence of manganese dioxide. Vilsmeier formylation was explored to prepare new formylated indole-2-carbaldehydes. Furthermore, the treatment of indole-2-carbaldehydes with nitromethane led to the formation of 2-nitrovinylindoles. Graphical abstract: